RESTORATION OF FRONTAL TEETH GROUPS WITH PARAPULPAR POSTS AND THEIR EFFICIENCY - Turumova Marjona (European Science Publishing, 2024)
Significant destruction of the crown part of the tooth is regarded as a disease that eventually leads to morphofunctional disorders of the dentition and the entire dental system. Therefore, early diagnosis of pathological restructuring of the dental system and knowledge of the pathogenesis of possible complications after tooth extraction are not of little importance, which, in turn, determine the indications for preventive orthopedic treatment. For effective treatment of the destroyed crown part of the tooth, all kinds of pin structures are used, the most "ancient" of which are parapulpar pin structures.
Keywords: Destruction of the crown part of the tooth, orthopedic treatment, pin structures, parapulpar pin (PPP).